Online tutorial (i-Learn) usage and students' performance : an empirical evidence in Malaysian University / Norzaidi Mohd Daud, Nasyitah Salehudin, Naura Nadira Khairuddin, Roslinda Razalek and Nuur Fadhlika Mohd Sani - Salehudin, Nasyitah; Khairuddin, Naura Nadira; Razalek, Roslinda (Faculty of Business Management, 2013)
This paper is attempts to determine the relationship between online tutorial usage and students' performance in Malaysian university context. This study was conducted at Universiti Teknologi MARA (UiTM) which 150 undergraduates participated in this survey. The study focuses only on the using I-LEARN and concerntrate only on the understanding how to apply the learning styles effectively. The results provide insights on how the students could adopt on using I-LEARN and could improve the understanding of learning using interactive online tutorials. This study is perhaps one of the first to address the I-Learn adoption for students to investigate their influences on learning performance.